EFEK LIKOPEN TERHADAP TIKUS PUTIH GALUR SD (Sprague Dawley) YANG DIINDUKSI PARASETAMOL DENGAN MELIHAT AKTIVITAS SGPT DALAM DARAH - Maysara, Risha; Yuliani, Sapto (Pharmaciana, 2011)
Liver is one of the most important organ for drug metabolism in the body. Thedamage to the liver can be marked by increased activity of the enzyme alanineaminotransferase (ALT) in the blood. Lycopene is an antioxidant that has the ability toeliminate free radicals and detoxifies electrophilic compounds that damage can beprevented. The purpose of this research is to know whether lycopene can inhibit theincrease alanine aminotransferase activity of SD (Sprague Dawley) rats induced byparasetamol. This experiment using 20 male rats Sprague Dawley. They were dividedinto 4 groups. Group I is a healthy control (baseline) was only given aquadest, group IIwere given paracetamol as pain control, group III and IV are treatment group wereeach given lycopene with a dosage 15 Âµg/kg BW and 30 Âµg/kg BW for 21 days. On 19thday group II, as well as all treatment groups induced paracetamol. The blood samplingwas performed on orbital sinus on 19th day (before induced by paracetamol) and on 21thday or two days after induced paracetamol to know the difference alanineaminotransferase activity. The data were analyzed using non-parametric statisticalmethods with Kruskal-Wallis test followed by Mann-Whitney test with 95% confidencelevel. The result has showed that the lycopene doses 15 Âµg/kgBW had alanineaminotransferase activity of 130.10 Â± 11.83 U/I and lycopene doses 30 Âµg/kgBW hadalanine aminotransferase activity of 106.46 Â± 2.36 U/I. If compared with paracetamolcontrol had alanine aminotransferase activity of 92.53 Â± 2.57 U/I, should take asummary that the lycopene doses 15 Ã¬g/kg BW and 30 Ã¬g/kg BW couldnât decreasealanine aminotransferase activity on SD (Sprague Dawley) male rats.